Structural Breaks Dan Volatilitas Harga Daging Ayam Berdasarkan Tingkatan Pasar Di Indonesia (Jurnal Agribisnis Indonesia, 2026)
Chicken meat is currently one of the most widely consumed sources of animal protein by the public. Crucial factors to ensure price stability and purchasing power include access to price information at all market levels. This study aims to analyze structural breaks and price volatility of chicken meat across different market levels in Indonesia. The data used in this study consists of daily chicken meat prices during the 2020–2024 period at the retail level across six islands in Indonesia (Java, Sumatera, Bali-NT, Kalimantan, Sulawesi, and Papua), covering prices across various market levels, including traditional markets, wholesalers, modern retailers and producers. This study employs the additive outlier model to analyze structural breaks and coefficient of variation (CV) analysis to examine volatility. The study indicates that chicken meat price fluctuations in Indonesia are generally stable, with low to moderate CV values, although structural breaks were found in several regions, reflecting varying price dynamics. Java shows relative stability, while the producer market in Papua experienced increased instability following a structural break. These findings suggest the need for regular price monitoring, strengthened distribution particularly in Papua and region-specific policy approaches. Further research is needed to identify the causes of structural breaks to support more accurate and effective policymaking.